Novel beta-carboline indole alkaloids from the leaves of Tabernaemontana elegans - Mansoor, TA (2012)
We have isolated three -carboline indole alkaloids (1-3) from the MeOH extract of the leaves of Tabernaemontana elegans. The chemical structures of these novel entities were established by means of spectroscopic techniques including 2D NMR spectroscopic experiments. The new skeletal features of compounds 1 and 2 were the presence of a two-carbon unit, attached to a structurally related -carboline skeleton, resulting in the formation of additional six and seven-membered new rings in 1 and 2, respectively. To the best of our knowledge, it appears to be the first report on the isolation of -carboline indole alkaloids from the genus Tabernaemontana. Compounds 1-3 were evaluated for their potential P-glycoprotein modulating properties using the rhodamine-123 assay, in both MDR1-gene transfected and parental mouse lymphoma cell lines. Compounds 1 and 3 exhibited a weak activity.